A combined phenolic extraction and fermentation reactor engineering model for multiphase red wine fermentation. Issue 1 (15th October 2019) - Miller, Konrad V.; Noguera, Roberto; Beaver, Jordan; Oberholster, Anita; Block, David E.
Abstract: Red wine production begins with a simultaneous fermentation and solid‐phase extraction process. Red wine color and mouthfeel is the result of the extraction of phenolics from grape skins and seeds during fermentation, where extraction is a strong function of temperature and ethanol concentration. During fermentation, grape solids form a porous "cap" at the top of the fermentor, resulting in a heterogeneous fermentation system with significant temperature and concentration gradients. In this work, we present a spatial, time‐variant reactor engineering model for phenolic extraction during red wine fermentation, incorporating fermentation kinetics, mass transfer, heat transfer, compressible fluid flow, and phenolic extraction kinetics. The temperature and ethanol concentration profiles predicted by this model allow for the calculation of phenolic extraction rates over the course of fermentation. Phenolic extraction predictions were validated against prior experimental data to good agreement and compared to a well‐mixed model's predictions to show the utility of a spatial model over well‐mixed models. Abstract : Red wine production begins with a simultaneous fermentation and solid‐phase extraction process. Red wine color and mouthfeel is the result of the extraction of phenolics from grape skins and seeds during fermentation, where extraction is a strong function of temperature and ethanol concentration. This work illustrates a reactor engineering model which predicts the spatial concentration of phenolics in heterogeneous unsteady state red wine fermentations.